A wizard of Earthsea - Le Guin, Ursula K. 1929- (Boston Houghton Mifflin, 2012)
A boy grows to manhood while attempting to subdue the evil he unleashed on the world as an apprentice to the Master Wizard.
"Houghton Mifflin Harcourt."
UCWS-2015-G-2223 donated by Prof. Eric Julian Manalastas
Keywords: Fantasy; Magic -- Fiction; Wizards -- Fiction